Expression of an epidermal growth factor-transdermal peptide fusion protein in Arabidopsis thaliana and its therapeutic effects on skin barrier repair - Yu, Guangdong; Lin, Shisheng; Huang, Xulong; Gao, Shuang; Song, Chengyang; Khalilov, Farid; Chen, Qiongzhen; Issaro, Nipatha; Xiao, Jiali; Xu, Xiashun; Wang, Junchao; Zhao, Wengang; et al. (Frontiers in Plant Science, 2025)
Epidermal growth factor (EGF) is recognized for its role in regulating keratinocyte proliferation and differentiation, thereby facilitating the restoration of impaired skin barriers. Nevertheless, challenges related to the penetration and safety of EGF remain to be resolved. In this study, we evaluated the efficacy of TDP1, a transdermal peptide, in enhancing the penetration of EGF through murine skin, utilizing EGF expressed in A. thaliana. The coding sequences of the TDP1 and EGF genes were cloned as a fusion construct into a plant expression vector. The resulting plasmid, pGM3301-TDP1-EGF, was introduced into A. thaliana via the floral dip method. Positive clones were identified using polymerase chain reaction (PCR). High-expression strains were selected through Western-blot analysis and enzyme-linked immunosorbent assay (ELISA). Homozygotes plants were obtained through self-pollination. The impact of the TDP1-EGF fusion protein on the restoration of a compromised epidermal barrier was assessed using dermatoscopy. Keratinocyte (KC) proliferation was examined via hematoxylin and eosin (H&E) staining, while KC differentiation, lipid synthesis, and inflammatory factors were analyzed using reverse transcription quantitative PCR (RT-qPCR) and immunohistochemistry. Compared to other expression systems, the A. thaliana system utilized for TDP1-EGF expression offers the advantages of being devoid of toxicity from endogenous plant substances, rendering it both safe and suitable for scalable production of the recombinant protein. The yield of the TDP1-EGF fusion protein expressed in A. thaliana accounted for 0.0166% of the total soluble protein. EGF conjugated with TDP1 displayed enhanced transdermal activity compared to unconjugated EGF, as evidenced by the Franz diffusion cell assay. Furthermore, the biological efficacy of the TDP1-EGF fusion protein surpassed that of EGF alone in ameliorating epidermal barrier damage in a murine skin injury model. This research has the potential to revolutionize the development and delivery of skincare products and establishes a foundation for the application of molecular farming in skin health.